2013
DOI: 10.1007/s13277-013-0712-4
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 5 promotes the proliferation and migration of human gastric carcinoma cells

Abstract: Aquaporin 5 (AQP5) promotes the progression and invasion of several cancers, but its role in the tumorigenesis of human gastric carcinoma (GC) has not been clearly defined. Here, we investigated the potential functions of AQP5 in the proliferation and migration of human GC. RT-PCR and western blotting were used to detect the expression of AQP5 in human GC cell lines. Immunohistochemistry was applied to evaluate the expression of AQP5 in human GC tissues and corresponding normal tissues. Following ectopic overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 26 publications
1
48
0
1
Order By: Relevance
“…Recently, Lee et al (11) reported that AQP5 overexpression is significantly associated with lymph node involvement and a poorer prognosis in patients with breast cancer, suggesting the value of AQP5 as a prognostic marker in breast cancer. Huang et al (18) also verified that AQP5 promotes the proliferation and migration of human gastric carcinoma cells. Wang et al (19) performed a study to show that AQP5 was mainly expressed in colorectal carcinoma cells and barely expressed in paraneoplastic normal tissues.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, Lee et al (11) reported that AQP5 overexpression is significantly associated with lymph node involvement and a poorer prognosis in patients with breast cancer, suggesting the value of AQP5 as a prognostic marker in breast cancer. Huang et al (18) also verified that AQP5 promotes the proliferation and migration of human gastric carcinoma cells. Wang et al (19) performed a study to show that AQP5 was mainly expressed in colorectal carcinoma cells and barely expressed in paraneoplastic normal tissues.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies indicated that AQP5 protein localized on the membrane of different kinds of cells such as corneal epithelium cells, acinar cells in the lacrimal gland and pulmonary epithelial cells [14]. Overexpression of AQP5 have been reported to be associated with many kinds of cancers such as colorectal, cervical, lung, breast and epithelial ovarian cancer, and to be a potential prognostic biomarkers [15-19]. The role of AQP5 in carcinogenesis is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that AQP5 protein localized on the membrane of different kinds of cells such as corneal epithelium cells, acinar cells in the lacrimal gland and pulmonary epithelial cells [14]. Overexpression of AQP5 have been reported to be associated with many kinds of cancers such as colorectal, cervical, lung, breast and epithelial ovarian cancer, and to be a potential prognostic biomarkers [15][16][17][18][19]. The role of AQP5 in carcinogenesis is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%